2016
DOI: 10.1371/journal.pone.0148799
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Delta Neutrophil Index and Myeloperoxidase Index for Predicting Acute Complicated Appendicitis in Children

Abstract: BackgroundIn children with acute appendicitis, 30% to 75% present with a complication, such as perforation, and the early diagnosis of complications is known to improve outcomes. Serum delta neutrophil index (DNI) and myeloperoxidase index (MPXI) are new inflammatory markers, and thus, in the present study, the authors evaluated the predictive values of these two markers for the presence of a complication in children with acute appendicitis.MethodsThis retrospective observational study was conducted on 105 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…In previous study by Kim et al 32 , the predictive role of DNI for complicated appendicitis was only fair with AUC of 0.738 in children. In general population, a sensitivity and specificity of the DNI for prediction of perforated appendicitis was reported to be 25.0%…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In previous study by Kim et al 32 , the predictive role of DNI for complicated appendicitis was only fair with AUC of 0.738 in children. In general population, a sensitivity and specificity of the DNI for prediction of perforated appendicitis was reported to be 25.0%…”
Section: Discussionmentioning
confidence: 85%
“…In children, several studies have indicated that serum CRP is a sensitive (83% to >90%) for detecting appendiceal perforation. 34,35 Kim et al 32 recently reported that serum CRP is a good predictor of complicated appendicitis, with a sensitivity of 69% and a specificity of 83% at a cut-off level of 4.0 mg/dL with an AUC of 0.840 on the ROC curve. In general population, a sensitivity and specificity of CRP for the prediction of perforated appendicitis was 80% and 69%, respectively, at a cut-off level of 9.52 mg/L.…”
mentioning
confidence: 99%
“…An increase in DNI of >12% at 72 h after ED admission predicted mortality in patients with neonatal sepsis (28). In a recent study, Kim et al (29) investigated the usefulness of DNI as an early predictor of acute complicated appendicitis in children, and observed a significantly higher median DNI in patients with acute complicated appendicitis (2.2%), compared with those with non-complicated appendicitis (0%; P <0.001) (29). Furthermore, a DNI cut-off value of 5.7% was used to determine 30-day mortality at the time of diagnosis of spontaneous bacterial peritonitis (30).…”
Section: Discussionmentioning
confidence: 99%
“…Studies for the role of DNI in differentiating perforated appendicitis from non‐perforated appendicitis have been conducted in the elderly and children . In previous studies, the predictive value of the DNI for complicated appendicitis was good with an AUC of 0.807 in the elderly and fair with an AUC of 0.738 in children.…”
Section: Discussionmentioning
confidence: 99%